Monetary Policy, Risk-Taking and Pricing: Evidence from a Quasi-Natural Experiment - Vasso Ioannidou; Steven Ongena; José-Luis Peydró (Review of Finance, 2015)
We study the risk-taking channel of monetary policy in Bolivia, a dollarized country where monetary changes are transmitted exogenously from the US. We find that a lower policy rate spurs the granting of riskier loans, to borrowers with worse credit histories, lower ex-ante internal ratings, and weaker ex-post performance (acutely so when the rate subsequently increases). Effects are stronger for small firms borrowing from multiple banks. To uniquely identify risk-taking we assess collateral coverage, expected returns and risk premia of the newly-granted riskier loans, finding that their returns and premia are actually lower, especially at banks suffering from agency problems.
Keywords: E44; G01; G21; G28; L14; 330; monetary policy; low short-term interest rates; softening lending standards; credit risk; liquidity risk; subprime borrowers; bank agency problems; duration analysis